Meta-Analysis: The Effect of E-Learning-Based Mind Mapping on Students' Critical Thinking Skills - Occe Luciana; Tomi Apra Santosa; Agus Rofi’i; Taqiyuddin Taqiyuddin; Bachtiar Nasution (Universitas Muhammadiyah Enrekang, 2023)
critical thinking skills. The type of research is meta-analysis research. The data sources in this meta-analysis research are 11 national and international journals that have been published from 2018-2023. The method of selecting data sources is the PRISMA method. The process of searching for data sources through Google Scholar, Eric and Proquest. The technique of collecting data sources is direct observation and documentation through the journal database. Data analysis is quantitative analysis by calculating the effect size value, standard error and average value (mean) with the help of the JSAP application. The results of this study indicate that the average effect size value is = 0.812 with high criteria. This finding explains that the e-learning-based mind mapping model has a significant effect on students' critical thinking skills. The e-learning-based mind mapping model fosters critical thinking skills so that it supports students' digital literacy in learning